Sistem Informasi Administrasi SDIT Mauritaniyyah - Muhammad Saputra; Muhammad Alan Wahyu Andrian; Rezkiyan Hikmah (Program Studi Teknik Komputer, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
Abstract— Mauritaniyyah Islamic Primary School in the midst of the Muslims answered about the importance of Islamic education. Strengthen and thicken faith, provide a good and correct understanding of Islamic teachings in accordance with the understanding of Ahlul Sunnah Wal Jama'ah. The purpose of this research is to create an administrative system that simplifies and speeds up the performance of admin staff. The method used in designing the posyandu administrative data processing system is the method of analysis and design of an object-oriented system (Object Oriented Modeling) using the Unified Modeling Language (UML) system development tools. The tests carried out are validation testing, questionnaire testing and application testing. The results of research on school administration information systems can help admins process data processing and reports at SDIT Mauritaniyyah to be fast, and accurate. After the authors design and analyze the administrative system, the authors can draw the conclusion that administration does not always develop with this program. Building this administrative application really takes time so that the results can be satisfactory.